2017
DOI: 10.1097/cad.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and influence on outcome of HER2/neu, HER3 and NRG1 expression in patients with metastatic colorectal cancer

Abstract: Our aim was to explore the impact of the HER2/neu, HER3 receptor as well as their ligands' neuregulin (NRG1) expression on the outcome of patients with metastatic colorectal cancer (mCRC). NRG1, HER2/neu and HER3 expression was evaluated in 208 patients with mCRC receiving 5-FU/LV plus irinotecan or irinotecan plus oxaliplatin as the first-line treatment. Biomarker expression was correlated with the outcome of patients. NRG1 (low: 192 vs. high: 16), HER2/neu (low: 201 vs. high: 7) and HER3 (low: 69 vs. high: 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…No evidence has convinced that HER2 gene amplification is a prognostic factor for CRC. Laurentpuig et al (2016) and Stahler et al (2017) demonstrated patients with HER2 amplification tumor had a worse survival, but some recent studies (Pietrantonio et al, 2017;Richman et al, 2016) argued no meaningful relationships between this marker and survival. Several studies had reported the frequency of BRAF mutation in Chinese CRC patients, but the number of samples was limited in most of the studies (Li et al, 2011a; Mao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No evidence has convinced that HER2 gene amplification is a prognostic factor for CRC. Laurentpuig et al (2016) and Stahler et al (2017) demonstrated patients with HER2 amplification tumor had a worse survival, but some recent studies (Pietrantonio et al, 2017;Richman et al, 2016) argued no meaningful relationships between this marker and survival. Several studies had reported the frequency of BRAF mutation in Chinese CRC patients, but the number of samples was limited in most of the studies (Li et al, 2011a; Mao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al (2011b) reported an association between HER2 expression and tumor size and distant metastases, and a recent meta-analysis showed HER2 amplification was associated with lymph node metastasis and advanced tumors stage (Sun et al, 2016). The number of studies suggests that HER2 may play some role in tumor progression and would be a valuable prognostic factor for CRC patients (Laurentpuig et al, 2016;Stahler et al, 2017). But in other studies, HER2 gene amplification was higher in patients with more advanced stage or distant metastases, and no significant difference in prognosis for CRC patients (Pietrantonio et al, 2017;Wang et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, many of the allele specific replication genes are reported to be cancerrelated (Supp Table 1). Notably, three genes that lose allelic replication in DKO1 cells, are also reported to be associated with colon cancer; NRG1 (Luraghi et al, 2017;Stahler et al, 2017), PCDH7 (Li et al, 2020;van Roy, 2014) and DLC1 (Durkin et al, 2007;Peng et al, 2013) (Fig. 5c,d and Supp Fig.…”
Section: Dna Hypomethylation Causes Loss Of Allelic Replicationmentioning
confidence: 93%
“…HER-2/neu is a member of the transmembrane epidermal growth factor receptor (EGF-R) family and is physiological expressed in many epithelial cells. However, it is overexpressed and/or amplified in human tumor of distinct origin including mammary carcinoma [ 8 ] and colorectal cancer [ 9 ]. HER-2/neu transformation is associated with an increased cell proliferation, migration, enhanced cell cycle progression as well as a survival of patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%